2005
DOI: 10.1097/01.ico.0000153558.67031.15
|View full text |Cite
|
Sign up to set email alerts
|

Deep Lamellar Endothelial Keratoplasty: Surgery in Complex Cases With Severe Preoperative Visual Loss

Abstract: DLEK surgery can be used in cases with severe visual loss caused by bullous keratopathy with transfer of healthy donor endothelium, clearing of the central cornea, and restoration of useful vision. DLEK also can be successfully combined with other intraocular surgeries such as vitrectomy, intraocular lens exchange, and sutured intraocular lens surgery. The DLEK graft can tolerate subsequent intraocular surgery performed as early as 3 months after placement of the donor tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…[34][35][36][37] Other authors 38,39 also adopted the DLEK procedure and reported good success in their patients even when it was combined with other intraocular procedures. 40 Melles et al 41 again revolutionized the field by instituting a significant modification to facilitate greatly the PLK procedure-they described a technique in which they simply stripped the Descemet membrane from the recipient, thus converting the DLEK procedure to the procedure known as DSEK (Fig. 5).…”
Section: Posterior Lamellar Keratoplastymentioning
confidence: 98%
“…[34][35][36][37] Other authors 38,39 also adopted the DLEK procedure and reported good success in their patients even when it was combined with other intraocular procedures. 40 Melles et al 41 again revolutionized the field by instituting a significant modification to facilitate greatly the PLK procedure-they described a technique in which they simply stripped the Descemet membrane from the recipient, thus converting the DLEK procedure to the procedure known as DSEK (Fig. 5).…”
Section: Posterior Lamellar Keratoplastymentioning
confidence: 98%
“…Fogla et al observed an average endothelial cell count of 1,732 cells/mm 2 , which reflects a 15% endothelial cell loss at 6 months [33]. Amayem et al evaluated the endothelial cell loss in six patients after complex case 9-mm DLEK [30]. Mean endothelial cell loss at 6 and 12 months was 48 and 65%, respectively.…”
Section: Plk/dlekmentioning
confidence: 96%
“…Amayem et al performed DLEK surgery on six patients with severe bullous keratopathy and preoperative vision between light perception and counting fingers [30]. DLEK was combined with vitrectomy and placement of a ciliary sulcus IOL in four patients and with cataract surgery in one patient.…”
Section: Effect Of Concomitant Proceduresmentioning
confidence: 99%
See 2 more Smart Citations